Atmospheres of stillness in Bristol's Bearpit. (February 2017) - Buser, Michael
This paper studies atmospheres of stillness in a contested urban public space known as the 'Bearpit'. The purpose is to provide a nuanced account of stillness and its relationship to atmosphere. Drawing on an ethnographic examination of the Bearpit, the paper finds that the positive and beneficial aspects of stillness can be found in unexpected and unconventional places. However, there is no single, unifying experience of stillness, but rather a plurality of 'stillings'. The paper highlights three forms of stillness distilled from study of the site – calmness, control and withdrawnness – and demonstrates how these modalities emerge from and contribute to the construction of atmospheres in the Bearpit. Moreover, these atmospheres have direct political consequences for those who take part in city life. The paper's contribution is found in the advancement of non-anthropocentric understandings of atmosphere and the development of stillness as a way of understanding city life.